Preferred M2 Polarization by ASC-Based Hydrogel Accelerated Angiogenesis and Myogenesis in Volumetric Muscle Loss Rats - Hong Huang; Jiejie Liu; Haojie Hao; Deyun Chen; Ling Zhizhong; Meirong Li; Haijing Song; Rong Xiang; Chaoguang Jiang; Xiaobing Fu; Weidong Han (Hindawi Limited, 2017)
Volumetric muscle loss (VML) injury resulted from massive muscle defects and diseases for which there are still no effective therapeutic treatments. This study aimed to investigate the effects of rat adipose-derived mesenchymal stem cells (rASCs) and rASCs-conditioned medium- (CM-) based type I collagen hydrogel on macrophage (MP) transition, myogenesis, and vascularization in the rat VML model. Laser Doppler results demonstrated much higher blood flow in the rASC- and CM-based hydrogel groups. qRT-PCR, hematoxylin and eosin, immunofluorescence, and Sirius Red staining manifested that both rASCs and CM-based hydrogel implantation accelerated muscle repair with upregulated angiogenesis and myogenesis, attenuated inflammation while facilitating M2 transition, and decreased the collagen deposition compared with the hydrogel group. In vitro experiments indicated that factors secreted from polarized M2 MPs could accelerate the migration and tube formation capacities of HUVECs. These results suggested that rASCs exerted immunomodulatory effects on MPs which further enhanced the proangiogenic potential on ECs to promote myogenesis and angiogenesis during muscle repair. These fundamental results support further clinical applications of ASCs for muscle loss injury.